ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНДА ХАЛЫҚТЫҢ БӘНТЛИГИ ҲӘМ СОЦИАЛ - ЭКОНОМИКАЛЫҚ ӨЗГЕРИСЛЕР - Торебаев, О.; Алиева, Г. (SCIENCE and SOCIETY, 2016)
The article is devoted to the issues of labour employment in the conditions of the market economy in the country, liquidation of unemployment and other labor market regulations. The opportunities of occupied employment, issues of implementation of youth occupation have been studied in the article.